Nonperturbative mass renormalization effects in nonrelativistic quantum electrodynamics - Davis M. Welakuh; Vasil Rokaj; Michael Ruggenthaler; Angel Rubio (Physical Review Research)
In this work we investigate the effects that multimode photonic environments, e.g., optical cavities, have on the properties of quantum matter. We highlight the importance of the nonperturbative mass renormalization procedure for ab initio quantum electrodynamics simulations and how it connects to common approximations used in polaritonic chemistry and cavity materials engineering. We focus on one-dimensional systems which can be solved exactly for large number of photon modes. First, we apply mass renormalization to free particles. The value of the renormalized mass depends on the details of the photonic environment and on the number of particles. We then show how the multimode photon field influences various ground- and excited-state properties of atomic and molecular systems. For instance, we observe the enhancement of particle confinement in the binding potential for the atomic system, and the modification of the potential energy surfaces of the molecular dimer due to photon-mediated long-range interactions. We also highlight how these changes compare to the common free-space mass-renormalization approximation employed in electronic structure theory and quantum chemistry. Since such phenomena are enhanced under strong light-matter coupling in a cavity environment they will become relevant for the emerging fields of polaritonic chemistry and cavity materials engineering.